Polarographic Determination of Tetraethyl Lead in Gasoline - Viswanatham, C. R.; Vats, S. S. (Defence Science Journal, 2014)
The polarographic determination of tetra-ethyl lead in gasoline by the hydrochloric acid axtraction method of Borup and Levin has been critically studied and an improved procedure employing a solution of hydrogen chloride in ether is described.